SAS in the Gulf War the story behind bravo two zero and the hunt for Saddam's scud missiles - Crawford, Steve 1960- (AMBER Books LTD, 2019)
Drawing upon unpublished accounts from SAS soldiers who fought in the war, as well as previously classified information, SAS in the Gulf War paints a vivid picture of what it's like to fight as an elite soldier, and what SAS operations were actually like behind Iraqi lines. Read about the special relationship that developed between SAS soldiers and the Royal Air Force helicopter crews who flew teams deep into enemy-held territory; the heartrending story of the patrol code-named "Bravo Two Zero"; the breathtaking tales of combat between SAS mobile fighting columns and Iraqi Scud launcher teams; and the successful SAS role in the collation of intelligence from the Kuwaiti resistance. In addition, the book serves as the definitive guide to every aspect of SAS operations in the Gulf War, from where it fit in strategically to the cooperation between the SAS and US elite units stationed there.